The Effect of Performance-Based Regional Expenditure Revenue Budget and Good Government Governance on Performance Accountability of Local Government Institutions in Tambrauw Regency, West Papua Province - Amandus Yesyan; Maryam Mangantar; Joy Elly Tulung (Research Parks Publishers, 2021)
The results of the regression equation can show that the constant value -2.020 can be interpreted if all independent variables are considered constant, namely: Performance-Based Regional Budget (X1) variable, Good Government Governance (X2) variable, then the value of the dependent variable, namely: Performance Accountability of Local Government Agencies (Y), is 2,020 units. The regression coefficient value of the Performance-Based Budget (X1) variable is 0.615, this value means that if there is an increase of 1 unit in the Performance-Based APBD variable (X1), while the Good Government Governance (X2) variable is considered constant, then the variable dependent, namely Performance Accountability of Local Government Agencies (Y), will increase by 0.615 units. The regression coefficient value of the Good Government Governance (X2) variable is 0, 555 this value means that if there is an increase of 1 unit in the Good Government Governance variable (X2), while the Performance-Based APBD variable (X1) is considered constant, then the dependent variable, namely the Accountability of Performance of Local Government Agencies (Y), will increase by 0.555 units. Furthermore, to determine the effect of the independent variables partially on the dependent variable, the t-test was used. If the value of t < t1-, (n-2) or p>0.05, then H0 is accepted and Ha is rejected. The Performance-Based Regional Budget (X1) variable produces a positive direction with a tcount of 4.839 with a probability of 0.000. Because the probability value (sig) t < 5% (0.000 < 0, 05) then partially the Performance-Based APBD variable (X1) has a positive and significant effect on the Performance Accountability variable of Local Government Agencies (Y) if the Good Government Governance (X2) variable remains in value. Thus, the hypothesis which states that there is a positive and significant effect of the Performance-Based APBD variable (X1) on the Regional Government Agency Performance Accountability variable (Y) is accepted. The Good Government Governance (X2) variable produces a positive direction with a tcount of 4.357 with a probability of 0.000. Because the probability value (sig) t < 5% (0.000 < 0.05) then partially the Good Government Governance (X2) (X2) variable has a significant positive effect on the Regional Government Agency Performance Accountability variable (Y) if the Performance-Based APBD variable (X1 ) remains the value. Thus the hypothesis which states that there is a positive and significant effect of the Good Government Governance (X2) variable on the Regional Government Agency Performance Accountability variable (Y) is accepted. The calculation results show that all independent variables can be declared to have a positive and significant effect. R Squrae value or the number of coefficients of determination. The magnitude of the coefficient of determination in the table above is 0.492 or equal to 49.2%. This figure means that 49.2% of the resulting Local Government Agency Performance Accountability variable (Y) can be explained by using the Performance-Based APBD variable (X1) and the Good Government Governance variable (X2). Based on the results of the study, it was found that the Performance-Based Budget had a positive and significant effect on the Performance Accountability variable of Local Government Agencies (Y) in Tambrauw Regency, West Papua Province. This means that the better the performance-based APBD is implemented, the better the Performance Accountability of Local Government Agencies.